Factors associated with medication adherence among diabetic patients attending diabetic center, Lalitpur. - Dhungel,Sushma (2017)
ABSTRACT: Diabetes Mellitus is a major global health problem. Poor medication adherence in patients with diabetes has been associated with poor glycemic control increasing complication rates, costs and mortality. The aim of the present study is to evaluate the factors associated with medication adherence among diabetic patients. A Cross sectional descriptive study and non-probability sampling technique was used among 101 selected diabetic patients attending Kathmandu Diabetes and Thyroid Center Pvt.Ltd Jawalakhel. Data was collected by interviewing the patients using structured questionnaire with Morisky, Green & Levin Adherence Scale to assess the medication adherence. The obtained information was entered in SPSS version 23 and analyzed using descriptive and inferential statistics such as frequency, percentage, mean, standard deviation, interquartile range and chi-square. The study has found out that majority of patients (63.4%) had medium level of adherence, high adherence (34.7%) and low adherence (2.0%) with antidiabetic medications. Majority of patients (87.1%) had adequate level of knowledge regarding the disease. Studied sociodemographic characteristics, health related factors and knowledge related factors were not significantly associated with medication adherence level. Adherence to antidiabetic medication was found to be medium. Studied variables did not affect the medication adherence. For improving the adherence level among diabetic patient's helpful methods like using pill boxes and medication dose reminders into their daily routine should be incorporated. Periodically, awareness program to a group or individual counseling regarding the consequences of non-adherence should be created.